Evaluating adjunct professors for promotion: a case study approach to review adjunct student evaluation of teachers over time - Cruz-Boone, Christine; Boschini, Debbie; Sherman, Tamarra (Center for Leadership Equity and Research)
Student assessment of courses and instructors can provide meaningful data about effective educational practices. Adjunct faculty make-up the majority of teachers in higher education but they are often not evaluated consistently or promoted to permanent faculty. Instead, evaluations of adjunct faculty are primarily used to identify inadequacies. The deficit thinking model argues that educational leaders should not use the term at-risk as a pretense to explain student outcomes. Similarly, this study argues for the extension of the deficit thinking model to adjunct faculty. This retrospective mixed-methods case study investigated student feedback for one higher education teacher to understand procedures or best practices in the process of self-analysis for teaching effectiveness. The three emergent themes from the study included instructor effectiveness (69.47%), course effectiveness (18.56%), and areas of improvement (11.97%). Findings indicate that in some instances educational leaders in higher education should shift thinking about the way contingent faculty are evaluated, promoted, and included in academic institutions.